Trunk strength effect on track wheelchair start: implications for classification - Vanlandewijck, Y. C.; Verellen, J.; Beckman, E.; Connick, M.; Tweedy, S. M. (Medicine & Science in Sports & Exercise, 2011)
Purpose: The T54 wheelchair racing class comprises athletes with normal arm muscle strength and trunk strength ranging from partial to normal. Paralympic sports classes should comprise athletes who have impairments that cause a comparable degree of activity limitation. On the basis of this criterion, the purpose of this study was to determine whether the T54 class is valid by assessing the strength of association between trunk strength and wheelchair acceleration.